2014
DOI: 10.3389/fpubh.2014.00102
|View full text |Cite
|
Sign up to set email alerts
|

Religious Affiliation as a Predictor of Involuntary Psychiatric Admission: A Brazilian 1-Year Follow-Up Study

Abstract: Objective: The aim of this study was to analyze factors associated with the legal status at psychiatric admission of individuals with psychosis or bipolar disorder in a Latin-American cultural setting.Methods: Prospective observational study was conducted in São Paulo, Brazil. We analyzed 169 individuals with bipolar or psychotic disorder in need of hospitalization. Sociodemographic data, data on the psychiatric disorder, information about the hospital stay, and data at time of discharge were collected. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The full meta-analysis results are presented in table 2 and a meta-analysis restricted to high-quality studies is presented in table 3. Forest plots are available in the appendix (pp [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full meta-analysis results are presented in table 2 and a meta-analysis restricted to high-quality studies is presented in table 3. Forest plots are available in the appendix (pp [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…89 Two studies noted no effect. 34,35 The association between involuntary hospitalisation and risk to self was widely reported, although whether the assessment of risk was based on previous self-harm or suicide attempts, or expressions of suicidal ideation, was often unclear. Nine studies found that suicidal behaviour, ideation, and history were associated with voluntary rather than involuntary hospitali sati on.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inpatient unit serves a catchment area of 501,351 residents on an area of 4,298.38 km 2 , with a population density of 116 inhabitants per km 2 (ISTAT 2015). The unit has 17 beds.…”
Section: Setting and Samplementioning
confidence: 99%
“…In Brazil, as reflected in the study of Casella and Loch [17] religious affiliation was determined as a predictor of involuntary psychiatric admission. The study involved eighty eight patients who were voluntarily admitted and eighty one involuntarily admitted.…”
Section: Presentationmentioning
confidence: 99%